Peningkatan Hasil Belajar Materi Pertumbuhan dan Perkembangan Melalui Model Pembelajaran Everyone Is A Teacher - ., Ruwiyati . (Universitas Tanjungpura, 2017)
Implementation of learning in the classroom is one of the main tasks of teachers, and learning can be defined as activities aimed at membelajarkan students. In the learning process is still often found their tendency to minimize the involvement of students. The dominance of the teacher in the learning process leads to the tendency of students more passive so that they are more waiting serving teachers than to seek and find their own knowledge, skills or attitudes that they need. Determination of improper strategy can be fatal, can cause failure of learning. Here of course the task of teachers trying to make learning more exciting and fun for all the students. The strategy was instrumental in creating active learning and fun. One of the active learning strategy is a strategy Everyone Is A Teacher. This strategy is one of the strategies in active learning model (active learning). Learning Strategies Everyone Is A Teacher is a learning strategy that is used by educators with the intention of asking learners to become speakers all play against all his friends in the classroom learning